2012
DOI: 10.1108/13620431211283788
|View full text |Cite
|
Sign up to set email alerts
|

Testing the impact of emotional labor on work exhaustion for three distinct emergency medical service (EMS) samples

Abstract: 2012),"Testing the impact of emotional labor on work exhaustion for three distinct emergency medical service (EMS) samples", Career Development International, Vol. 17 Iss 7 pp. 626 -645 Permanent link to this document: http://dx.If you would like to write for this, or any other Emerald publication, then please use our Emerald for Authors service information about how to choose which publication to write for and submission guidelines are available for all. Please visit www.emeraldinsight.com/authors for more in… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

2
41
0
4

Year Published

2014
2014
2024
2024

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 39 publications
(47 citation statements)
references
References 64 publications
2
41
0
4
Order By: Relevance
“…For example, one type of deep acting technique is cognitive change which involves reappraisal of a situation to lessen its emotional impact, for example, thinking about how a patient would feel. 18 Decreased perceived physical health was related to higher intent to leave the EMS profession 12,16 as well as work exhaustion. 18 The EMS work is physically demanding.…”
Section: Importance Of Understanding Why Ems Professionals Leave the mentioning
confidence: 99%
See 3 more Smart Citations
“…For example, one type of deep acting technique is cognitive change which involves reappraisal of a situation to lessen its emotional impact, for example, thinking about how a patient would feel. 18 Decreased perceived physical health was related to higher intent to leave the EMS profession 12,16 as well as work exhaustion. 18 The EMS work is physically demanding.…”
Section: Importance Of Understanding Why Ems Professionals Leave the mentioning
confidence: 99%
“…18 Decreased perceived physical health was related to higher intent to leave the EMS profession 12,16 as well as work exhaustion. 18 The EMS work is physically demanding. Studnek et al 21 found that 26% of their large EMS sample was obese and that three-quarters of the respondents did not meet the Center for Disease Control recommendations for physical activity.…”
Section: Importance Of Understanding Why Ems Professionals Leave the mentioning
confidence: 99%
See 2 more Smart Citations
“…HEMS pilots were considered an appropriate population for this study's purposes because of their demanding psychosocial work environment. Their work requires high cognitive effort 25) and includes high emotional demands 26) and a highly unpredictable workload. Irrespective of their demanding work characteristics, HEMS pilots reported relatively high levels of wellbeing in a previous study which suggests that they were healthy and felt competent to do their jobs 27) .…”
mentioning
confidence: 99%